Effective relationship engagement in the post-integration of mergers and acquisitions - Jedin, Mohd. Haniff; Md Saad, Norsafinas (2016)
Research on the relationship engagement in mergers and acquisitions (M&As) is still unclear although this phenomenon has been explored in the global multi-business environments.Furthermore, existing research does not clearly demonstrate the role of relationship among M&A players within the amalgamation processes between acquirer and the acquired firm.Hence, this paper addresses the factors that related to the relationship engagement among the M&A players particularly from the perspectives of Malaysian acquirers.This paper highlights four major indicators on effective relationship engagement: Collaboration, face to face interaction, on-line communication and collegial relationships between the acquirer and the acquired firms.Drawing from the extant literature, hypotheses are developed, elaborating success factors to improve the M&A integration performance through relationship engagement initiatives.